2016
DOI: 10.1039/c6ob01584k
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a tailor made anion receptor into the side chain of small peptides allows fine-tuning the thermodynamic signature of peptide–DNA binding

Abstract: The binding between peptides and DNA is often driven by entropic forces. We demonstrate herein a new approach to shift the thermodynamic profile of peptide/DNA binding from entropy to enthalpy driven. This eventually leads to higher compacted DNA aggregates which are important for gene transfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…(Holliday junctions are cross-shaped structures formed by four double-stranded segments of DNA in which each DNA molecule participates in two segments(112)). An analysis of B-factors from X-ray crystal structures suggested that the most enthalpically favorable interactions (i.e., interactions involving highly polarizable anions) incurred strong entropic penalties that resulted from reduced intermolecular mobility.The observations of Freire, Klebe, Berg, and Ho (and many others(58,66,94)), are qualitatively consistent with the simplified description of H/S compensation initially proposed by Williams and Dunitz: When molecules bind tightly (favorable enthalpy), they incur conformational constraints (unfavorable entropy). This succinct description clearly helps rationalize some binding phenomena.…”
supporting
confidence: 84%
“…(Holliday junctions are cross-shaped structures formed by four double-stranded segments of DNA in which each DNA molecule participates in two segments(112)). An analysis of B-factors from X-ray crystal structures suggested that the most enthalpically favorable interactions (i.e., interactions involving highly polarizable anions) incurred strong entropic penalties that resulted from reduced intermolecular mobility.The observations of Freire, Klebe, Berg, and Ho (and many others(58,66,94)), are qualitatively consistent with the simplified description of H/S compensation initially proposed by Williams and Dunitz: When molecules bind tightly (favorable enthalpy), they incur conformational constraints (unfavorable entropy). This succinct description clearly helps rationalize some binding phenomena.…”
supporting
confidence: 84%
“…Thus, the binding affinity of a series of tetrapeptides 34 ( a – e ) (Figure a) consisting of a different number of GCP and lysine residues was tested using calf thymus DNA (ctDNA). The results showed that binding became more enthalpy favored with an increasing number of GCP groups, compared to the free lysine residues (Figure b) . Therefore, the introduction of GCP moieties into the peptide could effectively alter the thermodynamic signature of peptide/DNA binding from an entropy driven process to an enthalpy driven one.…”
Section: Rational Design and Potential Application Of Gcp-based Molec...mentioning
confidence: 99%
“…3 The GCP-motif, which was developed by Carsten Schmuck, acts as a strong oxoanion-binder, so that especially its coupling to or combination with other cationic amino acids (such as lysine or arginine) has been important. The resulting GCP-lysine and GCParginine conjugates have been applied in anion-recoginition, 4,5,6 materials chemistry 7,8,9 and genetransfection. 10,11,12 To broaden the synthetic applicability of amino-acid derived building blocks, synthetic strategies other than the classical amide-coupling have been developed.…”
Section: Introductionmentioning
confidence: 99%